2017
DOI: 10.5530/ptb.2017.3.9
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Antidiabetic Activity of Sulforaphane

Abstract: Background: Sulforaphane is mainly found in cruciferous vegetables. It is a glucosidal prodrug with many pharmacological activities like anti oxidant, anti ulcer, anti viral etc. The present work aims the screening of in vitro anti diabetic activity of Sulforaphane from broccoli extract. Method: The Hypoglycemic activity was performed with amylase inhibition assay by using chromogenic DNSA method. In this percentage inhibition of analyte was compared with that of control to conclude the proved anti diabetic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Sulforaphane is a dietary phytochemical (a secondary plant metabolite) with low toxicity and is widely consumed in cruciferous vegetables and many dietary nutraceuticals. It has been extensively studied in the past several years for its health benefits in various in vitro and in vivo studies, which have reported its anti-diabetic [139][140][141], anti-inflammatory [138], and anti-obesity [142] effects in human and model animals. For example, it exerts cytoprotective effects on mice by increasing the expression of several antioxidant proteins [143].…”
Section: Potential Health Benefitsmentioning
confidence: 99%
“…Sulforaphane is a dietary phytochemical (a secondary plant metabolite) with low toxicity and is widely consumed in cruciferous vegetables and many dietary nutraceuticals. It has been extensively studied in the past several years for its health benefits in various in vitro and in vivo studies, which have reported its anti-diabetic [139][140][141], anti-inflammatory [138], and anti-obesity [142] effects in human and model animals. For example, it exerts cytoprotective effects on mice by increasing the expression of several antioxidant proteins [143].…”
Section: Potential Health Benefitsmentioning
confidence: 99%
“…A study conducted by [8] proved that 100; 250; and 500 μg of broccoli extract containing sulforaphane had inhibitory values of the alpha-amylase enzyme, respectively, 11.65; 36.38; and 46%. Furthermore, research by [9] proved that broccoli juice with a concentration of 10% (v/v) containing polyphenols and flavonoids was able to inhibit the alpha-glucosidase enzyme by 36%.…”
Section: Mechanism Of Inhibition Of Alpha-amylase and Alpha-glucosida...mentioning
confidence: 99%
“…Broccoli contains various compounds such as flavonoids, alkaloids, saponins, and steroids [6], as well as antioxidants [7]. Broccoli can lower blood sugar levels by various mechanisms, such as inhibition of alpha-amylase and alpha-glucosidase enzymes, increased expression of GLUT4, inhibition of DPP-IV (Dipeptidyl peptidase-4) enzymes, and Nrf2 activation [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The interest in finding inhibitors that can block or delay carbohydrate hydrolysis with enzymes such as alpha-glucosidases and reduce the accumulation of sugar is shaping research in diabetes treatment [ 55 ]. Studies have demonstrated that most natural antioxidants in plant sprouts can exert the action of defense mechanisms against oxidative stress and inhibit primary enzymes which hydrolyze carbohydrates into simple sugars [ 56 , 57 , 58 , 59 ]. In addition, the formation of advanced glycation end-products (AGEs) is prevalent in diabetic patients and can contribute to the development of osteoporosis [ 60 ].…”
Section: Health Benefits Of Sproutsmentioning
confidence: 99%